Limiting of unsatisfactory weight loss among overweight women after nutritional intervention - Souza Lopes, Mariana; Gonçalves Barbosa, Maria Júlia; Ferreira, Nathália Luíza; dos Santos, Luana Caroline; Souza Lopes, Aline Cristine (O Mundo da Saúde, 2016)
Insufficient weight loss in interventions conducted with overweight individuals demonstrate the need to identify their predictors in order to redirect actions and promote greater success. Thus, we aimed to identify predictors of unsatisfactory weight loss among overweight women after nutritional monitoring in Primary Health Care. This was a retrospective study of overweight women after 12 months of monthly individual nutritional monitoring. Data were collected through anamnesis containing sociodemographic data, reported morbidities, habits and food consumption, as well as anthropometric measurements. The weight loss was classified as unsatisfactory (<5% of initial weight) and satisfactory (≥5%), and these groups were compared using the Student’s t-test, Mann Whitney, Chi-square and Fisher’s Exact statistical tests. (p < 0.05). 62.9% of the 70 participants (n=44) presented unsatisfactory weight loss. They were aged 52.6±11.9 years old who on average had a monthly per capita income of 63.6% of minimum salary (18.6%; 198.3%), ; characteristics similar to those women who progressed satisfactorily. Those with unsatisfactory weight loss presented a greater prevalence of hypertension, slept less hours per night, watched TV or used computer for longer periods of time, and reported less sweating during physical activity at the start of monitoring. The results show that the failure to lose weight may be related to aspects that go beyond the adoption of adequate food, including factors such as sleep, physical inactivity, and comorbidities. It is therefore suggested that the development of differentiated and expanded interventions regarding the therapeutic approach, consider the complexity involved in instituting more effective, healthy, and satisfying weight-loss programs